2013
DOI: 10.4314/njp.v41i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practices of mothers of young children in Lagos, Nigeria

Abstract: months was significantly associated with lower parity (p=0.020) and higher maternal educational level. Those who had more than secondary education were 8 times more likely to practice EBF for 6 months than those with no formal education (OR 7.65,. Conclusion: Breastfeeding initiation and exclusivity for 6 months were inadequate. Promotion of good health-seeking behavior, maternal education and family planning are recommended in order to improve mothers' breastfeeding practices and infant nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
30
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 16 publications
11
30
1
3
Order By: Relevance
“…This low level of exclusive breast feeding practice among nursing mothers in Nigeria as observed in the present study, though also established in a number of other Nigerian studies, the prevalence of exclusive breastfeeding appear to vary across and within the regions from 10% -56% [13]- [19], with a few studies reporting prevalence rates above 50% [18] [19]. This varying levels of prevalence rates observed, may not only be due to the differing methodologies and exclusive breast feeding definitions adopted by these studies, but to existing risk factors such as socio-demographics, customs, attitudes, beliefs and women's work conditions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This low level of exclusive breast feeding practice among nursing mothers in Nigeria as observed in the present study, though also established in a number of other Nigerian studies, the prevalence of exclusive breastfeeding appear to vary across and within the regions from 10% -56% [13]- [19], with a few studies reporting prevalence rates above 50% [18] [19]. This varying levels of prevalence rates observed, may not only be due to the differing methodologies and exclusive breast feeding definitions adopted by these studies, but to existing risk factors such as socio-demographics, customs, attitudes, beliefs and women's work conditions.…”
Section: Discussionsupporting
confidence: 85%
“…This is probably due to the fact that, they are better able to comprehend the benefits and consequences within the context of existing customs, traditions, social and environmental constraints. This association of exclusive breastfeeding with the level of maternal educational has also been observed consistently in various studies [18] [19] [20] [22]- [27].…”
Section: Discussionsupporting
confidence: 78%
“…The finding of this study shows that 16.4% of mothers practice exclusive breastfeeding. A prevalence of 82% has however been reported in Lagos Nigeria 10 and 31% in Sokoto, Nigeria, 15 . In East Asia Pacific, it was found that 43% mothers practiced exclusive breastfeeding and 41% in East/South Africa 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, it was found out that the rate of breastfeeding initiation within 1hr was l5% 9 . Another study in Lagos Nigeria, found that 59.2% of mothers initiated breastfeeding within one hour after birth 10 . Early breastfeeding initiation has been found to increase mother to child bonding, regulate infant temperature, breathing and enhance breastfeeding longevity 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Optimal breastfeeding practice, including early initiation and exclusive breastfeeding, is associated with positive health effects on both mother and child [1–8]. One way to achieve optimal breastfeeding is to promote ‘breastfeeding on demand’.…”
Section: Introductionmentioning
confidence: 99%